2003
DOI: 10.1002/pon.671
|View full text |Cite
|
Sign up to set email alerts
|

Do sociodemographic and disease‐related variables influence benefit‐finding in cancer patients?

Abstract: This study examined patients' perceptions that having cancer led to positive life changes, or benefit-finding (BF), e.g. improved relationships, enhanced appreciation of life, increased resilience and self-reliance. We investigated the relations between BF, sociodemographic (e.g. gender, age, marital status, education, income) and disease-related variables (e.g. severity of disease or cancer stage, time since diagnosis). The sample was comprised of 83 men and women with various types of cancer, and all 4 stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
183
7
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(230 citation statements)
references
References 23 publications
30
183
7
10
Order By: Relevance
“…Nevertheless, we found significant negative correlations between PWB and PTGI total scores: people with lower PWB reported greater PTG. Physical symptoms may remind patients of the threat caused by their illness and, as other studies have shown, greater feelings of threat may prompt more positive changes (PTG) (Barakat et al 2006;Lechner et al 2003). In addition, positive correlations were reported between SFWB and PTGI total scores, indicating that patients with greater perceived social support experienced more positive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found significant negative correlations between PWB and PTGI total scores: people with lower PWB reported greater PTG. Physical symptoms may remind patients of the threat caused by their illness and, as other studies have shown, greater feelings of threat may prompt more positive changes (PTG) (Barakat et al 2006;Lechner et al 2003). In addition, positive correlations were reported between SFWB and PTGI total scores, indicating that patients with greater perceived social support experienced more positive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on SES is contradictory: higher benefit finding has been reported among lower SES women (Tomich & Helgeson, 2004), among higher-income women (Cordova et al, 2001), and among women with more education (Sears, Stanton & Danoff-Burg, 2003). There is evidence that higher disease stage induces greater benefit (Tomich & Helgeson, 2004) at least up to Stage II cancers (Lechner et al, 2003), consistent with the idea that stress induces benefit. Also consistent with that interpretation, one study found a positive relation of stress with some measures of benefit finding (Sears et al, 2003); another found a similar relation, but only if the cancer experience met the criteria for post-traumatic stress disorder (Cordova et al, 2001).…”
Section: What Factors Promote Benefit Finding?mentioning
confidence: 94%
“…In the cancer literature, there is some indication that benefit finding occurs more among minority women (Tomich & Helgeson, 2004) and patients who are younger (Lechner et al, 2003). Evidence on SES is contradictory: higher benefit finding has been reported among lower SES women (Tomich & Helgeson, 2004), among higher-income women (Cordova et al, 2001), and among women with more education (Sears, Stanton & Danoff-Burg, 2003).…”
Section: What Factors Promote Benefit Finding?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although recently, the study of BF has gained attention from the scope of psychooncology, most studies have focused on adult patients (Antoni et al, 2001;Bower & Segerstrom, 2004;Carver & Antoni, 2004;Cordova, Cunningham, Carlson & Andrykowsi, 2001;Cruess et al, 2000;Lechner, Antoni & Zakowski, 2002;Lechner, Carver, Antoni, Weaver & Phillips, 2006;Lechner, Zakowski & Antoni, 2003;McGregor et al 2004;Mols, Vingerhoets, Coebergh & van den Poll-France, 2009;Reiker et al, 1985;Sears et al 2003;Thornton, 2002;Tomich & Helgeson, 2004;Weaver, Llabre, Lechner, Penedo & Antoni, 2008). The results of these studies have shown that most of the survivors report positive consequences such as: the development of closer bonds with relatives and/or friends, a more sensitive approach or greater interest in religion and/or spirituality, as well as a more positive life scope.…”
Section: Post-traumatic Growth (Ptg) Benefit Finding (Bf) and Paediamentioning
confidence: 99%